Peak power assessment in isokinetic dynamometry - Iossifidou, A. N.; Baltzopoulos, V. (European Journal of Applied Physiology, 2000)
The purpose of the present study was to establish a method by which to derive accurate and valid isokinetic peak power measurements. For this purpose, peak power was calculated as the product of: (1) preselected angular velocity and peak moment without considering the angular velocity at peak moment (method I), (2) actual angular velocity and the respective moment values at that time (method II), (3) instant actual angular velocity at the point of peak moment and peak moment (method III), and (4) actual constant angular velocity and the highest moment during this period (method IV). Ten subjects performed concentric knee extensions at 30, 90, 180 and 300°/s on a Lido Active isokinetic dynamometer. The product of moment and actual angular velocity derived from the angular displacement data was used to measure peak power in methods II, III and IV. Significant differences were found between the four methods. Method I results in artificial peak power and methods II and III do not produce actual isokinetic peak power. The latter can only be assessed using method IV. It was concluded that method IV (highest moment during constant angular velocity period) must be used in order to obtain valid, accurate and comparable isokinetic peak power values.